Survey of in vitro fertilization add-ons in Japan (Izanami project) - Shionoya, N.; Yamada, M.; Harada, S.; Shirasawa, H.; Jwa, S. Chik; Kuroda, K.; Harada, M.; Osuga, Y. (Frontiers in Endocrinology, 2024)
Objective: To identify any correlations between evidence levels, adoption rates, and additional costs of in vitro fertilization (IVF) add-ons. Design: Online survey Subjects: The survey was conducted in 621 assisted reproductive technology-registered facilities that are members of the Japanese Society of Obstetrics and Gynecology from December 22, 2021, to February 13, 2022. Exposure: The survey included details regarding the specific add-on modalities employed and their associated costs; inquiries pertained to the fertility healthcare infrastructure in Japan before the implementation of the National Health Insurance scheme. Main Outcome Measures: The correlation between the adoption rate and cost of IVF add-ons and their evidence levels were analyzed. The evidence level of the add-on treatments was classified into Green, Amber, and Red categories based on the United Kingdom’s Human Fertilisation and Embryology Authority and Cochrane systematic reviews. Results: A total of 438 eligible responses were analyzed, with clinics constituting 70.9% of the respondents’ facilities. A total of 18 add-ons were assessed, and 96.5% (423/438) of facilities used at least one add-on. A positive correlation of the adoption rate and an inverse correlation of the cost with the evidence level of the IVF add-on treatment were observed (not significant). Outpatient clinics, defined as medical facilities with no beds, had a significantly higher adoption rate (Amber, 65.7%; Red, 52.0%) of add-ons than other facilities, regardless of the evidence rating, although the costs were similar across all site attributes. Conclusion: Accumulating evidence on the efficacy and safety of add-ons will lead to the development of medical care with a high-cost benefit, as an increase in the adoption rate and a decrease in cost are expected when limiting to medical care with a high level of evidence.